Intercropping Maize with Legumes for Sustainable Highland Maize Production - Adirek Punyalue (2018)
© 2018 Punyalue et al. Residue burning to prepare soil for maize growing deprives the soil of both protective cover and organic matter, and it exacerbates environmental issues such as Southeast Asia's haze problem. This paper reports on a study that evaluated the effectiveness of maize/legume intercropping as an alternative to maize cultivation with residue burning. Cowpea (Vigna unguiculata), mung bean (V. radiata), rice bean (V. umbellata), and lablab (Lablab purpureus) were sown into a standing maize crop 30 days before harvest, and the results were compared with a maize crop grown using residue burning as the method for land preparation at Pang Da Agricultural Station in Chiang Mai, Thailand, in a replicated trial conducted over 3 growing seasons from 2012 to 2014. Intercropping increased maize grain yield by 31-53% and left 70-170% more residue containing 113-230% more nitrogen than the maize sown after residue burning, depending on the legume, and decreased weed dry weight by two-thirds after 2 seasons. Soil biodiversity was enriched by the intercrops, with a doubling in the spore density of arbuscular mycorrhizal fungi in the root-zone soil and increased abundance, diversity (Shannon index), and richness of the soil macrofauna. The abundance of soil animals increased with crop residue dry weight (r = 0.90, P < 0.05) and nitrogen content (r = 0.98, P < 0.01). The effect of intercropping on maize grain yield and accumulation of residue and nitrogen were then confirmed in a participatory experiment involving farmers in 2 highland villages in the Phrao and Chiang Dao districts of Chiang Mai Province with maize and rice bean in 2015. The effects of maize/legume intercropping-increased nitrogen accumulation and crop residue, enhanced soil biodiversity, suppression of weeds, and protection of the soil surface, which enabled the maize to be sown without land clearing with fire-should all contribute to sustainable highland maize production.